Effect of noise reduction on evaluation of apical root resorption in digital radiography: An in vitro study - Mojdeh Mehdizadeh; Nazi Bonyanian (Isfahan University of Medical Sciences, 2013)
Introduction: One of the benefits of digital radiographs is the ability to process the image with software programs and increase the accuracy of diagnosis with image processing options. The present study was aimed at evaluating the effect of noise reduction on assessment of apical root resorption in enhanced digital radiographs processed by SCANORA software.Materials and methods: In the present experimental study, 60 extracted lower premolars with sound roots were used. The teeth were fixed in a dry human mandible for radiographic evaluation. Digital radiographs were taken before and after artificial external root resorption on the mesial side of the apical third by a #¼ round bur and transferred to SCANORA software. Then all the radiographs were examined by one radiologist twice, with and without the option of noise reduction, with a one-week interval between the readings. The radiographs were scored in two groups: 0 and 1, without and with root resorption, respectively. Resorptions were measured by Williams probe and considered as the gold standard. Data collected from the digital radiographs were processed and the gold standard values were analyzed by SPSS 11.5 using McNemar and Cochran tests (α = 0.05).Results: There were significant differences in frequencies of detection of root resorption between the three groups (standard, processed with the noise reduction option and processed without the noise reduction option) (p value < 0.001). There were no significant differences between the group processed with the noise reduction option and the group processed without the noise reduction option (p value = 0.774).Conclusion: Based on the results of this study application of noise reduction option in SCANORA software has no effect on the diagnosis of periapical lesions. Key words: Digital radiography, Image processing, Noise, Root resorption